2015
DOI: 10.1007/s11164-015-2186-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and crystal structure of modified benzophenone UV-absorber containing reactive group

Abstract: A modified benzophenone UV-absorber containing reactive group (4-(4,6-dichloro-1,3,5-triazin-2-yloxy)-2-hydroxyphenyl)phenyl)methanone (UV-DTHM) has been prepared in good yield from the nucleophilic substitution reaction of 2,4-dihydroxy benzophenone with 2,4,6-trichlorotriazine, catalyzed by 1.3 equiv. NaOH. The most favorable reaction conditions (the catalyst dosage, the mole ratio of the reactants, and reactive time) were selected. The compound was characterized by IR spectroscopy, 1 H NMR, 13 C NMR, mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…It has been shown that the proposed methodology of enzymatic preparation of laccase from Cerrena unicolor enables the attainment of a high activity value of 45 U/cm 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the proposed methodology of enzymatic preparation of laccase from Cerrena unicolor enables the attainment of a high activity value of 45 U/cm 3 .…”
Section: Discussionmentioning
confidence: 99%
“…New, ecological solutions rendering textiles bioactive and giving them barrier properties against ultraviolet (UV) radiation are the subject of studies carried out by many research groups [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…PVC is susceptible to photochemical degradation caused by the presence of abnormal structures that arise through side reactions during synthesis. , Various ultraviolet absorbers, including benzophenone and benzotriazole derivatives, have been reported to improve the light stability of PVC.…”
Section: Resultsmentioning
confidence: 99%
“…46 Women whose houses were decorated in the past 3 years had higher urinary concentrations of benzophenones than those whose houses were not decorated. Since benzophenones are commonly applied in paints due to their good thermal properties, 47 widespread presence of benzophenones in indoor air and house dust are well-noted. 48,49 We observed that participants who were engaged in physical activity every day had significant higher excretion levels of parabens (MeP and PrP) than those with no physical activity (less than 30 min of activity).…”
Section: Variations Of Urinary Concentrations Of Pcpcs Acrossmentioning
confidence: 99%